THE INFLUENCE OF INFLATION, CRUDE OIL PRICES, AND THE RAMADAN EFFECT ON STOCK RETURN - Supardi, Eviana Marvina; Rasyid, Rosmita (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to examine the effect of Inflation, Crude Oil Prices, and Ramadan Effect on Stock Return of manufacturing companies in Indonesia listed on the Indonesia Stock Exchange (IDX) during 2020. In this study, the sample selection technique used was purposive sampling with some predetermined criteria. This study shows that the independent variables in the form of Inflation and Crude Oil Prices have no effect on Stock Return. The other independent variable, Ramadan Effect shows a positive effect on Stock Return.